Modelling of an Elastomeric Composite Skin for a span-morphing aircraft wing - Alexander Shaw (ICAST 2014, 2014)
Span morphing is potentially one of the most advantageous forms of morphing, because it can allow a wing to have high aspect ratio at low speed when induced drag is critical, or to have lower aspect ratio at high speed when skin drag or structural loads can become design constraints. However it remains one of the harder forms of morphing to achieve without an excessive weight penalty, because of the requirement to add mechanisms to the wing box. Furthermore, the large changes in dimensions that are needed to make span morphing worthwhile mean that the wing skins used must be capable of handling large deformations. The ADaptive Aspect Ratio (ADAR) wing is a span-morph concept that features an Elastomeric Matrix Composite (EMC) skin in order to accommodate these large deformations. The EMC skin is an elastomeric material reinforced with fibers in the chordwise direction to suppress the in-plane Poisson ratio, which would otherwise lead to significant unwanted out-of-plane deformations in the final structure. The design of this skin is critical to the success of the ADAR wing, because there is a direct trade-off between the requirement for low deflections in response to aerodynamic loads, and the need to keep actuation forces as low as possible, to minimize the weight and power consumption of the actuators. The first requirement motivates a thick, stiff, and highly pre-stretched skin whereas the second motivates towards a thin, compliant membrane with minimal initial tension. This describes work towards a hyperelastic model of the material in an FE analysis of the structure, using a realistic section geometry and pressure distribution to estimate the deformation. The material model is validated with experimental data from sample material specimens. It is shown that the deformation of an elastomeric skin of this kind is very small under aerodynamic loading, and that therefore there is little aerodynamic penalty when using this type of wing.